1967
DOI: 10.1007/bf01376326
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of phosphorus sources of different availability by mycorrhizal and non-mycorrhizal maize

Abstract: The mycorrhizal relationship has interested biologists since its discovery by F r a n k 5. Since that time much study has been devoted to its occurrence and effect upon the associated higher plant. Our understanding of the mycorrhizal relationship is relatively advanced in the case of the ectotrophic mycorrhizas. The status of knowledge about the effect of the endotrophic vesicular-arbuscular mycorrhizae which occur on most crop plants, as well as many trees is, on the other hand, much more restricted. This la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
2

Year Published

1971
1971
2008
2008

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 9 publications
4
18
2
Order By: Relevance
“…These results are in sharp contrast to the observation by Murdoch et al (1967) that treatments with a readily available source of P produced no significant differences in P uptake or dry matter yield between mycorrhizal and nonmycorrhizal maize plants but with RP treatments, they obtained a much higher dry matter yield and P accumulation when plants were mycorrhizal. These workers and others (Hall et al, 1977;Mosse et al 1976) concluded that mycorrhizal plants could utilize rock phosphate fertilizers whereas non-mycorrhizal ones could not.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in sharp contrast to the observation by Murdoch et al (1967) that treatments with a readily available source of P produced no significant differences in P uptake or dry matter yield between mycorrhizal and nonmycorrhizal maize plants but with RP treatments, they obtained a much higher dry matter yield and P accumulation when plants were mycorrhizal. These workers and others (Hall et al, 1977;Mosse et al 1976) concluded that mycorrhizal plants could utilize rock phosphate fertilizers whereas non-mycorrhizal ones could not.…”
Section: Discussioncontrasting
confidence: 99%
“…The increased growth has been attributed to an enhanced nutrient uptake by the host plant (2,12,15,(18)(19)(20)26). Mycorrhizal plants take up more phosphorus than nonmycorrhizal controls when relatively unavailable sources of phosphorus are supplied to the roots (12,26).…”
Section: Methodsmentioning
confidence: 99%
“…The increased growth has been attributed to an enhanced nutrient uptake by the host plant (2,12,15,(18)(19)(20)26). Mycorrhizal plants take up more phosphorus than nonmycorrhizal controls when relatively unavailable sources of phosphorus are supplied to the roots (12,26). In most cases the addition of more readily available phosphorus eliminates differences in growth and phosphorus uptake (3,12,13,20,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence comparisons have been based on top yield and phosphorus uptake at a particular rate of application (e.g. Murdoch, Jacobs and Gerdemann 1967;Powell and Daniel, 1978). Moreover in most studies, the rate of application of the insoluble phosphorus sources was inadequate for «|aximum plant growth (for example, Daft and Nicolson, 1966;Powell and Daniel, 1978) This is not a valid comparison of the effect of VA mycorrhizas on the uptake of phosphorus from various sources of different solubilities, because the extent to which VA mycorrhizas increase phosphorus uptake and growth varies with phosphorus application rates (Abbott and Robson, 1977;Barrow, Malajczuk and Shaw 1977).…”
Section: Introductionmentioning
confidence: 99%